Optimizing Management of the Jeumpa Journal: Journal of Science & Biology Education, Journal of the Biology Education Department, Samudra University - Muhammad Khalil; Okhaifi Prasetyo; Muhammad Al Dilwan; Hasby Hasby (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Scientific journals are publication media that contain articles that present the results of research and scientific studies. Management of journals by departments at universities is essential in improving the quality and reputation of departments, especially in supporting the implementation of tridharma in research. Based on the results of observations, the management of the Jeumpa Journal carried out by the Department of Biology Education at Samudra University is still not optimal. Through the Community Partnership Program (PKM), efforts were made to solve problems related to the not yet optimal management of the journal. Together with Jeumpa Journal editorial partners, efforts to optimize the journal were carried out through four stages, namely optimizing the appearance of the journal's website, compiling author guidelines, compiling article templates, and socializing and promoting the journal. Evaluation with Jeumpa Journal editorial partners on all stages of optimization activities that have been carried out is used as a benchmark in preparing follow-up programs in the development.